PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MANAJEMEN PENDIDIKAN MAHASISWA STKIP PGRI BANDAR LAMPUNG - Hidayat, Nurdin (Lentera: Jurnal Ilmiah Kependidikan, 2020)
This Experimental Research aims to determine the Effect of Problem Based Learning Models on Learning Outcomes of Student Management Education in the Economic Education Study Program STKIP PGRI Bandar Lampung. This study uses an experimental method, the population in this study are students of the Economic Education Study Program STKIP PGRI Bandar Lampung, sampling using a purposive random sampling technique, based on the results of the study concluded that There is an Effect of Problem Based Learning Model on Learning Outcomes of Student Education Management STKIP PGRI Bandar Lampung